Analysis of Sharad Joshi’s Satirical Style: With Special Reference to “Jadoo Ki Sarkar”: शरद जोशी की व्यंग्य शैली का विश्लेषण: ‘जादू की सरकार’ के विशेष संदर्भ में - Meena, Geetanjali (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Sharad Joshi is a Hindi satirist who has effectively exposed deep social contradictions, political deceit, and the psychological structure of the common man through humor. In his writings, satire is not merely a means of entertainment but emerges as a medium for awakening social consciousness. In the story “Jadoo Ki Sarkar,” the author symbolically presents the public’s blind faith in power, belief in miracles, and the tendency to seek quick solutions to problems. The “magic” in the story actually represents the illusion through which ordinary citizens hope to find relief from their sufferings. This narrative shows how society, avoiding real struggle, becomes attracted to imaginary solutions. A balanced combination of humor and pathos is evident in the story. The reader, while smiling, is also internally disturbed, because the satire directly strikes at social reality. This work becomes a mirror of the mindset of contemporary Indian society, its political consciousness, and social inequalities. In conclusion, it can be said that “Jadoo Ki Sarkar” is a powerful example of Sharad Joshi’s satirical vision, in which he reveals the hopes, illusions, and helplessness of the common man. This story remains relevant even today and proves that Sharad Joshi’s satire transcends the boundaries of time and inspires social self-reflection. Abstract in Hindi Language: शरद जोशी हिंदी साहित्य के ऐसे व्यंग्यकार हैं जिन्होंने हास्य के माध्यम से समाज की गहरी विसंगतियों, राजनीतिक छल-प्रपंच और आम आदमी की मानसिक संरचना को प्रभावशाली ढंग से उजागर किया है। उनकी रचनाओं में व्यंग्य केवल मनोरंजन का साधन नहीं, बल्कि सामाजिक चेतना जगाने का माध्यम बनकर उभरता है। ‘जादू की सरकार’ कहानी में लेखक ने सत्ता के प्रति जनता की अंधी आस्था, चमत्कारों में विश्वास तथा समस्याओं के त्वरित समाधान की मानसिकता को प्रतीकात्मक रूप में प्रस्तुत किया है। कहानी का ‘जादू’ वस्तुतः उस भ्रम का प्रतिनिधित्व करता है, जिसके सहारे आम नागरिक अपने दुख-दर्द से मुक्ति की आशा करता है। यह कथा दर्शाती है कि किस प्रकार समाज वास्तविक संघर्ष से बचकर काल्पनिक उपायों की ओर आकर्षित होता है। कहानी में हास्य और करुणा का संतुलित संयोजन दिखाई देता है। पाठक मुस्कराते हुए भी भीतर से विचलित होता है, क्योंकि व्यंग्य सीधे सामाजिक यथार्थ पर प्रहार करता है। यह रचना समकालीन भारतीय समाज की मानसिकता, राजनीतिक चेतना और सामाजिक असमानताओं का दर्पण बन जाती है। निष्कर्षतः कहा जा सकता है कि ‘जादू की सरकार’ शरद जोशी की व्यंग्य-दृष्टि का सशक्त उदाहरण है, जिसमें वे आम आदमी की आशाओं, भ्रमों और विवशताओं को उजागर करते हैं। यह कहानी आज भी प्रासंगिक है और सिद्ध करती है कि शरद जोशी का व्यंग्य समय की सीमाओं से परे जाकर सामाजिक आत्मचिंतन को प्रेरित करता है। Keywords: शरद जोशी, जादू की सरकार, व्यंग्य, सामाजिक विडंबना, कथा विश्लेषण, शैली विवेचन, रचनात्मक विवेचन।